Epipogium taiwanense, a detail morphological description and additional new record to mainland China - Wu, Xun-Feng; Liu, Qiang; Tang, Ying; Chi, Kuan-Bo; Wang, Yu-Qian; Pang, Xin; Huang, Yao-Hua; Peng, Pei-Hao (Phytotaxa, 2020)
Epipogium taiwanense, is published in the book of Illustrated Flora of Taiwan in 2018. However, here only the specimen and simply descriptions were existed on which the protologue was based. Plant and flowers characteristics were not described in enough detail in the original description. Fortunately, it was rediscovered from Yunnan and Sichuan Province, China. It is morphological similar to E. aphyllum, but it can be easily distinguished from the latter by having large size flower bract (2.0 × 1.0 cm, significantly longer than pedicel and ovary), epichile of labellum concave with 1 longitudinal ridge on mid-lobe and the spur strongly recurve in the apex connecting with bottom of mid-lobe. A preliminary risk-of-extinction assessment, according to the IUCN Red List Categories and Criteria, is given for the newly recorded species.